IMRT with concomitant boost versus conventional radiation in the setting of sequential chemoradiotherapy for oropharyngeal cancer. Issue 4 (12th May 2014) - Franchin, Giovanni; Furlan, Carlo; Vaccher, Emanuela; Talamini, Renato; Gobitti, Carlo; Grando, Giuseppe; Minatel, Emilio; Dassie, Andrea; Trovò, Mauro Gaetano; Barzan, Luigi
Abstract Objectives The aim of this study was to assess the efficacy of IMRT with concomitant boost simultaneous integrated boost-intensity modulated radiotherapy (SIB-IMRT) compared with conventional radiation in the setting of sequential chemoradiotherapy (induction chemoradiotherapy(ICRT)) for patients with advanced oropharynx cancer (OPC). Materials and methods A single-institutional retrospective review was conducted on 84 patients (conventional radiation, n = 36; SIB-IMRT, n = 48) with stage III and IV OPC, who underwent definitive ICRT from 2002 to 2012. The study endpoints included overall survival (OS) and locoregional control (LRC). Results The median follow-up of the matched cohorts resulted similar (30 months for 3D-radiation technique versus 37 months for IMRT), and baseline characteristics were generally balanced between the two groups. However, patients managed with conventional radiation were less likely to have positron emission tomography-computed tomography (PET-CT) for staging and to receive induction chemotherapy with TPF. A multivariate Cox proportional hazard model showed that OS and LRC were associated with several known prognostic factors, along with radiation modality (SIB-IMRT versus conventional radiation, hazard ratio 0·27, p = 0·004; hazard ratio 0·31, p = 0·006; for OS and LRC, respectively). Conclusions The adoption of SIB-IMRT versus conventional radiation may produce a clinical benefit in OS and LRC among patients receiving ICRT for advanced OPC.